2019
DOI: 10.1016/j.cegh.2018.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of plasma leakage phase of dengue in resource limited settings

Abstract: The pathophysiology of severe dengue is related to increased capillary permeability and plasma leakage into extracellular space. A simple, low cost risk prediction tool for plasma leakage will be useful for clinicians practicing in rural areas without imaging facilities. Study design: A prospective observational study was carried out over 12 months at the National Hospital, Sri Lanka enrolling patients with confirmed diagnosis (via NS1 antigen testing) of early dengue infection. Clinical features on admission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…A similar study carried out in the same hospital showed an association of liver tenderness in early infection and plasma leakage. Therefore, presence of early hepatitis in this subgroup cannot be ruled out [25].…”
Section: Discussionmentioning
confidence: 99%
“…A similar study carried out in the same hospital showed an association of liver tenderness in early infection and plasma leakage. Therefore, presence of early hepatitis in this subgroup cannot be ruled out [25].…”
Section: Discussionmentioning
confidence: 99%
“…CDS aims to record natural history of dengue fever and build a comprehensive predictive model to identify people at risk of plasma leakage, early in the infection. The details of this collaborative project led by investigators of University of Colombo, Sri Lanka and University of New South Wales, Australia has been published previously [9,22]. In brief, CDS recruits' adults clinically suspected of having dengue fever (as evaluated by two independent medical officers to meet the clinical case definition of dengue [13]) admitted to NHSL within the first three days of fever.…”
Section: Methodsmentioning
confidence: 99%
“…The sample size calculation for CDS has been published previously [9,22] and this costing study includes all patients recruited to CDS by February 2020 (Phase 1 of CDS). All costs are indicated in United States dollars (USD) in the main manuscript and in Sri Lankan Rupees (LKR) in the S1-S5 Tables, using the average exchange rate of one United States dollar to 185.43 LKR in 2020.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations